Sustainable synthesis, antiproliferative and acetylcholinesterase inhibition of 1,4-and 1,2-naphthoquinone derivatives - Cabral, Rafaela G. (2023)
This work describes the design, sustainable synthesis, evaluation of electrochemical and biological properties against HepG2 cell lines, and AChE enzymes of different substituted derivatives of 1,4- and 1,2-naphthoquinones (NQ). A microwave-assisted protocol was optimized with success for the synthesis of the 2-substituted-1,4-NQ series and extended to the 4-substituted-1,2-NQ family, providing an alternative and more sustainable approach to the synthesis of naphthoquinones. The electrochemical properties were studied by cyclic voltammetry, and the redox potentials related to the molecular structural characteristics and the biological properties. Compounds were tested for their potential anti-cancer activity against a hepatocellular carcinoma cell line, HepG2, using MTT assay, and 1,2-NQ derivatives were found to be more active than their 1,4-NQ homologues (3a-f), with the highest cytotoxic potential found for compound 4a (EC50 = 3 mu M). The same trend was found for the inhibitory action against acetylcholinesterase, with 1,2-NQ derivatives showing higher inhibition(50 mu M) than their 1,4-NQ homologues, with 4h being the most potent compound (Inhibition(50 mu M) = 85%). Docking studies were performed for the 1,2-NQ derivatives with the highest inhibitions, showing dual binding interactions with both CAS and PAS sites, while the less active 1,4-NQ derivatives showed interactions with PAS and the mid-gorge region.